Initiator-free solid-state battery, preparation method and application thereof
By using in-situ solidification technology of electrolyte without initiators in lithium-ion batteries, the problem of flammable and explosive at high temperatures and the energy density is close to the limit, achieving higher electrochemical performance and cycle Lifespan enhances battery safety.
Patent Information
- Application Number
- CN202410511433.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-04-26
AI Technical Summary
Existing liquid lithium-ion batteries are flammable and explosive at high temperatures, and their energy density is close to the limit, which cannot be further improved, affecting the performance and safety of new energy vehicles.
The in-situ solidification technology of electrolyte without initiator is adopted. By injecting carbonate-based electrolyte and small molecule monomer into the dry battery cell, the pre-solid liquid is formed and then heated and polymerized to achieve solidification of the electrolyte.
It significantly improves the electrochemical performance and cycle life of solid-state batteries, avoids gas problems and residual effects generated by initiators, and enhances the safety of the batteries.
Smart Images

Figure CN118380633B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to an initiator-free solid-state battery, a preparation method thereof and applications thereof. Background Art
[0002] At present, lithium-ion batteries have been widely used, but with the continuous upgrading and changes in market demand, lithium-ion batteries can no longer meet the performance requirements of new energy vehicles in terms of energy density or safety, and there is an urgent need to iterate and upgrade the technology.
[0003] First, the current liquid lithium-ion battery electrolyte uses carbonate organic solvents, which are generally highly volatile and have low flash points. They are flammable and explosive at higher temperatures and have certain toxicity, which limits the application temperature range of liquid lithium-ion batteries. When the battery temperature is too high due to overcharging, improper use, etc., or when it is subjected to violent external collisions and extrusions, the electrolyte will overflow, which can easily lead to thermal runaway of the battery.
[0004] Secondly, the current energy density of liquid lithium-ion batteries is close to its limit energy density (300Wh / Kg). Since the voltage window of liquid electrolytes is limited and electrochemical decomposition is prone to occur, the possibility and difficulty of increasing the energy density of liquid batteries in the future are relatively high, and further breakthroughs cannot be achieved. The limited energy density of lithium-ion batteries will bring mileage anxiety to new energy vehicle users.
[0005] At present, the most effective solution to the above two problems is to introduce the in-situ solidification technology of electrolyte into liquid lithium-ion batteries. In-situ solidification technology is to add a small amount of small molecule monomers into the electrolyte and inject it into the dry battery cell. After the dry battery cell is completely soaked, the monomers in the electrolyte are polymerized under certain conditions to form a polymer network, thereby firmly locking the liquid electrolyte in the polymer network structure to form a solid electrolyte.
[0006] The in-situ solidification technology of electrolyte has the following advantages: (1) Because the electrolyte is in-situ solidified after being infiltrated into the battery, a good lithium ion path can be formed in the electrode after the electrolyte is solidified, and a buffer layer is formed between the solid electrode and the solid electrolyte to reduce the interface impedance. Therefore, the electrochemical performance of the high-energy density battery is less affected after the electrolyte is in-situ solidified; (2) After the electrolyte is in-situ solidified, it has basically no fluidity, which greatly alleviates the side reactions between the electrolyte and the electrode; in addition, the electrolyte solidified on the surface of the electrode and in the solid electrolyte can effectively prevent the oxygen generated by the positive electrode from crosstalking to the negative electrode due to its small porosity, thereby improving the safety of the high-energy density battery; (3) After the electrolyte is in-situ solidified, there is only a very small amount of free electrolyte inside the high-energy density battery. Therefore, when the battery is overcharged, abused and short-circuited to generate a large amount of heat, the probability of thermal runaway of the battery will be greatly reduced.
[0007] At present, the small molecule monomers added to the electrolyte are mainly generated by adding azo initiators (such as azobisisobutyronitrile) or peroxide initiators (such as dibenzoyl peroxide) to generate free radicals by heating to initiate the polymerization of the small molecule monomers, and then the in-situ solid-state battery is subjected to formation and other performance tests. However, this in-situ solid-state battery prepared by initiator-induced polymerization has the following disadvantages: (1) When the initiator is heated and decomposed to generate free radicals, it will also produce gases such as N2 or CO2, causing some bubbles to be generated inside the in-situ solid-state battery, blocking the transmission channel of lithium ions and thus affecting the electrochemical performance; (2) The residual initiator that has not been completely decomposed will affect the electrical performance of the in-situ solid-state battery and reduce its safety performance; (3) During the formation process of the in-situ solid-state battery, since the electrolyte has been solidified, the gas generated during the formation of the SEI film cannot be discharged into the air bag in time, which greatly affects its film forming performance and cycle life.
[0008] It can be seen that the electrochemical performance and cycle life of existing in-situ solid-state batteries need to be further improved.
[0009] In view of this, the present invention is proposed. Summary of the invention
[0010] The purpose of the present invention is to provide an initiator-free solid-state battery, a preparation method and application thereof, aiming to improve the electrochemical performance and cycle life of the in-situ solid-state battery.
[0011] The present invention is achieved in that:
[0012] In a first aspect, the present invention provides an initiator-free solid-state battery, which is prepared using a carbonate-based electrolyte, a small molecule monomer and a dry cell. The preparation method of the solid-state battery includes:
[0013] Injecting carbonate-based electrolyte into the dry cell, controlling the injection amount to be less than the designed injection amount of the dry cell;
[0014] Forming and charging a battery cell filled with a carbonate-based electrolyte;
[0015] The pre-solid solution formed by the small molecule monomer and the carbonate-based electrolyte is injected into the charged battery cell so that the injection volume reaches the designed injection volume of the dry battery cell, and then heated and polymerized.
[0016] In an optional embodiment, the ratio of the injection amount of the carbonate-based electrolyte in the dry battery cell to the designed injection amount of the dry battery cell is (0.3-0.7):1, preferably (0.4-0.6):1.
[0017] In an optional embodiment, in the pre-solid solution, the mass proportion of the carbonate-based electrolyte is 50%-85%, and the mass proportion of the small molecule monomer is 15%-50%.
[0018] In an alternative embodiment, the small molecule monomer has at least one carbon-carbon double bond;
[0019] Preferably, the small molecule monomer is selected from at least one of methyl methacrylate, glycidyl methacrylate, methoxypolyethylene glycol acrylate, methyl acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and pentaerythritol triacrylate.
[0020] In an optional embodiment, the carbonate-based electrolyte includes a lithium salt and a carbonate solvent, and the concentration of the lithium salt is 1.0 mol / L-2.0 mol / L;
[0021] Preferably, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluoroborate, lithium bis(oxalatoborate) and lithium difluorooxalatoborate; more preferably, the lithium salt is lithium hexafluorophosphate;
[0022] Preferably, the carbonate solvent is at least one of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, methyl formate, methyl acetate and ethyl propionate; more preferably, the carbonate solvent is a mixed solvent formed by ethylene carbonate and ethyl methyl carbonate, and the mass proportion of ethylene carbonate in the mixed solvent is 20%-40%.
[0023] In an optional embodiment, the dry battery cell includes a positive electrode sheet, a negative electrode sheet and a separator; the separator is arranged between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet is separated from the negative electrode sheet by the separator, and the positive electrode sheet is electrically connected to the negative electrode sheet through the separator.
[0024] In an optional embodiment, the battery cell filled with carbonate-based electrolyte is left to stand for 8h-20h, and then formed and charged to 3.8V-4.3V;
[0025] Preferably, the standing temperature is 40°C-50°C.
[0026] In an optional embodiment, the polymerization temperature is controlled to be 40° C.-60° C., and the polymerization time is 12 h-36 h.
[0027] In a second aspect, the present invention provides a method for preparing a solid-state battery according to any one of the aforementioned embodiments, comprising: injecting a carbonate-based electrolyte into a dry cell, and controlling the injection amount to be less than a designed injection amount of the dry cell;
[0028] Forming and charging a battery cell filled with a carbonate-based electrolyte;
[0029] The pre-solid solution formed by the small molecule monomer and the carbonate-based electrolyte is injected into the charged battery cell so that the injection volume reaches the designed injection volume of the dry battery cell, and then heated and polymerized.
[0030] In a third aspect, the present invention provides an electrical device, comprising a solid-state battery according to any one of the aforementioned embodiments or a solid-state battery prepared by the preparation method of the aforementioned embodiments.
[0031] The present invention has the following beneficial effects: firstly, a part of the carbonate-based electrolyte is injected into the battery cell for formation and charging, and then the pre-solid liquid formed by the small molecule monomer and the carbonate-based electrolyte is injected into the charged battery cell. Since the positive and negative electrodes in the charged battery cell will gather a large number of anions and cations on the surface under the action of the electric field, these ions can become active species, and quickly open the carbon-carbon double bonds of the small molecule monomers in the electrolyte at a higher temperature to initiate polymerization, so that the electrolyte in the battery is solidified. The preparation process provided by the present invention has the following advantages: the present invention first forms a stable SEI film and then solidifies it. Compared with the traditional method of solidifying first and then forming, it can significantly reduce the gas production in the SEI film formation process, which is beneficial to the improvement of the battery cycle life; the present invention can initiate the polymerization of small molecule monomers without adding an initiator, avoiding the gas production problem caused by adding an initiator, and there will be no initiator residue, which is beneficial to improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 This is a scanning electron microscope image of the disassembled positive electrode of the solid-state battery in Example 1;
[0034] Figure 2The charge and discharge curves of the solid-state batteries prepared in Example 1 and Comparative Example 1;
[0035] Figure 3 The charge and discharge curves of the solid-state battery prepared for Example 2 and Comparative Example 2;
[0036] Figure 4 The capacity retention rate curve of solid-state batteries after 100 charge and discharge cycles prepared in Example 1 and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0038] The embodiment of the present invention provides a method for preparing an initiator-free solid-state battery, which is prepared by using a carbonate-based electrolyte, a small molecule monomer and a dry battery cell, and comprises the following steps:
[0039] S1. Provide carbonate-based electrolytes, small molecule monomers and dry cells
[0040] The carbonate-based electrolyte includes a lithium salt and a carbonate solvent, and the lithium salt and the carbonate solvent are mixed evenly. In the actual operation process, the lithium salt is added to the carbonate solvent in a glove box filled with argon gas and stirred evenly.
[0041] In some embodiments, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate and lithium difluorooxalate borate, and the lithium salt may be any one or more of the above. In a preferred embodiment, the lithium salt may be lithium hexafluorophosphate (LiPF6), the raw material of lithium hexafluorophosphate is easily available, and it is beneficial to improve the electrochemical performance of the battery. By regulating the amount of lithium salt and carbonate solvent, the concentration of the lithium salt is 1.0 mol / L-2.0 mol / L, such as 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, etc.
[0042] In some embodiments, the carbonate solvent is at least one of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, methyl formate, methyl acetate and ethyl propionate, and the carbonate solvent can be any one or more of the above. In a preferred embodiment, the carbonate solvent is a mixed solvent formed by ethylene carbonate and ethyl methyl carbonate, and the mass proportion of ethylene carbonate in the mixed solvent is 20%-40% (such as 20%, 30%, 40%, etc.), and the mass proportion of ethyl methyl carbonate in the mixed solvent is 60%-80% (such as 60%, 70%, 80%, etc.).
[0043] In some embodiments, the small molecule monomer has at least one carbon-carbon double bond, and during the reaction, the carbon-carbon double bond opens and polymerizes, so that the electrolyte in the battery solidifies. The number of carbon-carbon double bonds can be 1, 2, 3, 4, etc., or more carbon-carbon double bonds can be contained, and the specific number is not limited.
[0044] In a preferred embodiment, the small molecule monomer is selected from at least one of methyl methacrylate, glycidyl methacrylate, methoxypolyethylene glycol acrylate, methyl acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and pentaerythritol triacrylate. The small molecule monomer can be any one or more of the above. The above small molecule monomers are all suitable for the preparation method provided in the embodiment of the present invention. Polymerization can be achieved by the method provided in the embodiment of the present invention without adding an initiator to obtain an in-situ solid-state battery.
[0045] In some embodiments, the dry cell includes a positive electrode sheet, a negative electrode sheet and a separator, which can be self-assembled or commercially available. The specific types of the positive electrode sheet, the negative electrode sheet and the separator are not limited.
[0046] Furthermore, the positive electrode active material in the positive electrode sheet includes at least one of a nickel-cobalt-manganese ternary positive electrode material and a lithium iron phosphate positive electrode material, and the positive electrode active material may be any one or two of the above. That is, the positive electrode sheet may be an NCM911 positive electrode sheet, but is not limited thereto. The negative electrode active material in the negative electrode sheet is selected from at least one of graphite, silicon, silicon carbon and silicon oxygen, and the negative electrode active material may be any one or more of the above. Specifically, the negative electrode sheet may be a silicon carbon 450 negative electrode sheet. The diaphragm is selected from at least one of a ceramic diaphragm, a polypropylene diaphragm and a polyethylene diaphragm, and the diaphragm may be any one or more of the above.
[0047] In some embodiments, the dry battery cell can be prepared into a soft pack by stacking NCM911 positive electrode sheets, silicon carbon 450 negative electrode sheets and ceramic diaphragm sheets, with a designed capacity of 1Ah, a designed liquid injection volume of 3g, and an energy density of 200Wh / Kg. The preparation process of the dry battery cell is as follows: stack, assemble and bake the homemade positive electrode sheets (specifically NCM911, with an active material loading of 94.5%), ceramic diaphragms and silicon carbon 450 negative electrode sheets (with an active material loading of 95.7%) to prepare the above-mentioned lithium-ion dry battery cells.
[0048] S2, injection of carbonate-based electrolyte
[0049] Inject the carbonate-based electrolyte into the dry battery cell, and control the injection amount of the carbonate-based electrolyte to be less than the designed injection amount of the dry battery cell, so as to leave a margin for the subsequent addition of small molecule monomers.
[0050] In some embodiments, the ratio of the amount of carbonate-based electrolyte injected into the dry cell to the designed injection amount of the dry cell is (0.3-0.7):1, preferably (0.4-0.6):1, and specifically can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, etc. For example, when the designed injection amount of the dry cell is 3g, the amount of carbonate-based electrolyte injected in step S2 can be 0.9g-2.1g, and specifically can be 0.9g, 1.5g, 2.1g, etc.
[0051] S3, formation and charging
[0052] The battery cell filled with carbonate-based electrolyte is formed and charged. The embodiment of the present invention performs formation before in-situ curing, which can improve the cycle life of the battery. The existing process is a method of preparing an in-situ solid-state battery first and then forming it, which will prevent the gas generated during the formation of the SEI film from being discharged into the air bag in time, thereby greatly affecting its film forming performance and cycle life.
[0053] In some embodiments, the battery cell filled with carbonate-based electrolyte is left to stand for 8h-20h, then formed and charged to 3.8V-4.3V, and the standing temperature may be 40°C-50°C. Long-term standing allows the carbonate-based electrolyte to be fully infiltrated and improves the uniformity of electrolyte distribution. The charging voltage is preferably within the above range. If the charging voltage is too small, the subsequent polymerization reaction cannot be triggered. If the charging voltage is too large, the battery cannot tolerate it.
[0054] Specifically, the standing temperature can be 40°C, 45°C, 50°C, etc., the standing time can be 8h, 10h, 15h, 20h, etc., and the voltage after charging can be 3.8V, 3.9V, 4.0V, 4.1V, 4.2V, 4.3V, etc.
[0055] S4, inject pre-solidified liquid and polymerize
[0056] The pre-solid liquid formed by small molecule monomers and carbonate-based electrolyte is injected into the charged battery cell to make the injection volume reach the designed injection volume of the dry battery cell, and then heated for polymerization. Because a large number of anions and cations will accumulate on the surface of the positive and negative electrodes in the charged battery cell under the action of the electric field, these ions can become active species, which can quickly open the carbon-carbon double bonds of the small molecule monomers in the electrolyte at a higher temperature to initiate polymerization, so that the electrolyte in the battery is solidified. According to its curing principle, this curing method can be called "high voltage ion polymerization method".
[0057] It should be noted that the preparation method provided by the embodiment of the present invention has the following advantages over the prior art: (1) The existing methods for preparing in-situ solid-state batteries mostly use azo or oxidizing initiators, which will generate gas during the curing process, causing uneven curing and thus damaging the performance of the in-situ solid-state battery. The high-voltage ion polymerization method used in the present invention does not use any initiator, so there is no problem of gas generation during the curing process. (2) There will be a large amount of initiator residue in the existing in-situ solid-state batteries, which not only affects the electrochemical performance, but also endangers the safety performance of the in-situ solid-state battery due to the extremely unstable initiator. However, in the present invention, no initiator is used, so there is no harm caused by the initiator residue.
[0058] In some embodiments, in the pre-solid solution, the mass proportion of the carbonate-based electrolyte is 50%-85%, and the mass proportion of the small molecule monomer is 15%-50%. The amount of the small molecule monomer added is preferably within the above range to further improve the electrochemical performance of the prepared solid-state battery.
[0059] Specifically, in the pre-solid liquid, the mass proportion of the carbonate-based electrolyte can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc., and the mass proportion of the small molecule monomer can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.
[0060] In some embodiments, the polymerization temperature is controlled to be 40°C-60°C, and the polymerization time is 12h-36h. The polymerization temperature and time are preferably controlled within the above range. If the polymerization temperature is too high or the polymerization time is too long, the formed SEI film is easily destroyed. If the polymerization temperature is too low, the polymerization rate is low, which prolongs the production cycle.
[0061] Specifically, the polymerization temperature can be 40°C, 45°C, 50°C, 55°C, 60°C, etc., and the polymerization time can be 12h, 15h, 20h, 25h, 30h, 36h, etc.
[0062] It should be added that the preparation method provided in the embodiment of the present invention does not require additional equipment and materials, has low energy consumption and low cost, is compatible with the existing lithium battery preparation process, and is therefore easy to industrialize.
[0063] An embodiment of the present invention further provides an initiator-free solid-state battery, which is prepared by the preparation method provided by the embodiment of the present invention. Since no initiator is added, it is beneficial to improve the cycle life and electrochemical performance of the battery.
[0064] The embodiment of the present invention further provides an electric device, including the solid-state battery provided in the embodiment of the present invention, and may also include an electric appliance, the specific type of which is not limited, and the solid-state battery is used to power the electric appliance. The electric device may be an electric car, a camera, a mobile phone, etc., and the specific type is not limited.
[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0066] It should be noted that the dry cells used in the following embodiments and comparative examples are homemade cells, and the preparation process of the dry cells is as follows: the homemade positive electrode sheets (specifically NCM911, with an active material loading of 94.5%), ceramic diaphragms and silicon carbon 450 negative electrode sheets (with an active material loading of 95.7%) are stacked, assembled and baked to prepare the required lithium-ion dry cells; the designed capacity is 1Ah, the designed liquid injection volume is 3g, and the energy density is 200Wh / Kg.
[0067] Embodiment 1
[0068] This embodiment provides a method for preparing an initiator-free solid-state battery, and the specific steps are as follows:
[0069] (1) In a glove box, LiPF6 was dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (the mass ratio of ethylene carbonate to ethyl methyl carbonate was 3:7) to prepare a 1.5 mol / L LiPF6 electrolyte.
[0070] (2) Inject the electrolyte in step (1) into the pre-prepared 1Ah soft-pack dry battery cell, with an injection volume of 1.5g.
[0071] (3) The battery cell filled with electrolyte obtained in step (2) is placed in an oven at 45°C for 12 hours to allow the electrolyte inside to fully infiltrate the battery cell, and then charged to 4.3 V by a small current to form a stable SEI film. The specific steps of the small current charging formation are as follows: charging to 3.0 V with a current of 0.02C, then charging to 3.4 V with a current of 0.05C, and finally charging to 4.3 V with a current of 0.1C.
[0072] (4) According to the mass fraction, 24% methyl methacrylate, 6% polyethylene glycol dimethacrylate (number average molecular weight Mn = 550) and 70% of the electrolyte in step (1) are mixed and stirred evenly to prepare a pre-solidified liquid. The prepared pre-solidified liquid is injected into the above-mentioned battery cell charged to 4.3V again, with an injection volume of 1.5g, and allowed to stand at room temperature for 24 hours to allow the pre-solidified liquid to fully infiltrate the battery cell, and then heated in a vacuum oven at 40°C for 36 hours to prepare an initiator-free in-situ solid-state battery.
[0073] The prepared in-situ solid-state battery was disassembled to observe the solidification of the electrolyte inside the battery. Figure 1 It can be seen that the electrolyte in the in-situ solid-state battery prepared in this embodiment has no liquid residue, and the electrolyte on the surface of the pole piece has been completely solidified and evenly coated on the surface of the pole piece, making it difficult to distinguish the particles on the pole piece in the SEM image, indicating that the initiator-free curing method used in the present invention has completely solidified the electrolyte.
[0074] The internal resistance and charge-discharge performance tests of the in-situ solid-state battery are shown in Table 1 and Figure 2 , Figure 4 The internal resistance and charge and discharge performance test methods are as follows: the internal resistance of the in-situ cured battery is directly tested by the Amber AT527L battery tester, and the charge and discharge performance is obtained by the Xinwei battery test system at 25°C with 0.1C charge and discharge, and the voltage range is: 2.75-4.3V.
[0075] Embodiment 2
[0076] This embodiment provides a method for preparing an initiator-free solid-state battery, and the specific steps are as follows:
[0077] (1) In a glove box, LiPF6 was dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (the mass ratio of ethylene carbonate to ethyl methyl carbonate was 3:7) to prepare a 1.5 mol / L LiPF6 electrolyte.
[0078] (2) Inject the electrolyte in step (1) into the pre-prepared 1Ah soft-pack dry battery cell, with an injection volume of 1.5g.
[0079] (3) The battery cell filled with electrolyte obtained in step (2) was placed in an oven at 45° C. for 12 h to allow the electrolyte inside to fully infiltrate the battery cell, and then charged with a small current to form a stable SEI film and then charged to 4.0 V. The specific steps of the small current charging formation are referred to Example 1.
[0080] (4) According to the mass fraction, 40% methyl acrylate, 10% polyethylene glycol diacrylate and 50% electrolyte of step (1) are stirred evenly to prepare a pre-solidified liquid; the prepared pre-solidified liquid is injected into the above-mentioned battery cell charged to 4.0 V again, and the injection amount is 1.5 g. The pre-solidified liquid is allowed to stand at room temperature for 24 hours to allow the pre-solidified liquid to fully infiltrate the battery cell, and then heated in a vacuum oven at 50°C for 24 hours to prepare an initiator-free in-situ solid-state battery.
[0081] Performance test: The prepared in-situ solid-state battery was disassembled to observe the solidification of the electrolyte inside the battery and to conduct performance tests such as internal resistance and charge and discharge on the in-situ solid-state battery. The results are shown in Table 1 and Figure 3 .
[0082] Embodiment 3
[0083] This embodiment provides a method for preparing an initiator-free solid-state battery, and the specific steps are as follows:
[0084] (1) In a glove box, LiPF6 was dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (the mass ratio of ethylene carbonate to ethyl methyl carbonate was 3:7) to prepare a 1.5 mol / L LiPF6 electrolyte.
[0085] (2) Inject the electrolyte in step (1) into the pre-prepared 1Ah soft-pack dry battery cell, with an injection volume of 1.5g.
[0086] (3) The battery cell filled with electrolyte obtained in step (2) was placed in an oven at 45° C. for 12 h to allow the electrolyte inside to fully infiltrate the battery cell, and then charged with a small current to form a stable SEI film and then charged to 3.8 V. The specific steps of the small current charging formation are as described in Example 1.
[0087] (4) According to the mass fraction, 80% of methoxy polyethylene glycol acrylate and 20% of polyethylene glycol diacrylate were stirred evenly to prepare a pre-solid liquid; the prepared pre-solid liquid was injected into the above-mentioned battery cell charged to 3.8V again, with an injection volume of 1.5g, and allowed to stand at room temperature for 24 hours to allow the pre-solid liquid to fully infiltrate the battery cell, and then heated in a vacuum oven at 60°C for 12 hours to prepare an initiator-free in-situ solid-state battery.
[0088] Performance test: The prepared in-situ solid-state battery was disassembled to observe the solidification of the electrolyte inside the battery and to conduct performance tests such as internal resistance and charge and discharge on the solid-state battery. The results are shown in Table 1.
[0089] Embodiment 4
[0090] The only difference from Example 1 is that the small molecule monomer is methyl methacrylate, and the total amount remains unchanged.
[0091] Embodiment 5
[0092] The only difference from Example 1 is that the small molecule monomer is polyethylene glycol dimethacrylate (Mn=550), and the total amount remains unchanged.
[0093] Embodiment 6
[0094] The only difference from Example 1 is that the small molecule monomer is pentaerythritol triacrylate, and the total amount used remains unchanged.
[0095] Embodiment 7
[0096] The only difference from the first embodiment is that the voltage after charging in step (3) is 3.5V.
[0097] Embodiment 8
[0098] The only difference from the first embodiment is that the voltage after charging in step (3) is 4.4V.
[0099] Embodiment 9
[0100] The only difference from Example 1 is that the heating temperature in step (4) is 30°C.
[0101] Embodiment 10
[0102] The only difference from Example 1 is that the heating temperature in step (4) is 70°C.
[0103] Comparative Example 1
[0104] This comparative example provides a method for preparing an existing solid-state battery, and the specific steps are as follows:
[0105] (1) In a glove box, LiPF6 was dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (the mass ratio of ethylene carbonate to ethyl methyl carbonate was 3:7) to prepare a 1.5 mol / L LiPF6 electrolyte.
[0106] (2) According to the mass fraction, 12% methyl methacrylate, 3% polyethylene glycol dimethacrylate, 85% electrolyte and 1% azobisisobutyronitrile accounting for the total mass of the two monomers are stirred evenly to prepare a pre-solid liquid; the prepared pre-solid liquid is injected into a 1Ah soft-pack dry battery cell with an injection volume of 3 g, and the cell is allowed to stand at room temperature for 24 hours to allow the pre-solid liquid to fully infiltrate the battery cell, and then heated in a vacuum oven at 45°C for 12 hours to prepare an in-situ solid-state battery with an initiator.
[0107] (3) The in-situ solid-state battery is charged and formed with a small current. The specific steps of the small current charging and formation are referred to Example 1.
[0108] Performance test: The prepared in-situ solid-state battery was disassembled to observe the solidification of the electrolyte inside the battery and to conduct performance tests such as internal resistance and charge and discharge on the in-situ solid-state battery. The results are shown in Table 1 and Figure 2 , 4 .
[0109] Comparative Example 2
[0110] This comparative example provides a method for preparing an existing solid-state battery, and the specific steps are as follows:
[0111] (1) In a glove box, LiPF6 was dissolved in a mixed solvent of ethylene carbonate and ethyl methyl carbonate (the mass ratio of ethylene carbonate to ethyl methyl carbonate was 3:7) to prepare a 1.5 mol / L LiPF6 electrolyte.
[0112] (2) According to the mass fraction, 20% methyl acrylate, 5% polyethylene glycol diacrylate, 75% electrolyte and 1% benzoyl peroxide of the total mass of the two monomers are mixed evenly to prepare a pre-solid liquid; the prepared pre-solid liquid is injected into a 1Ah soft-pack dry battery cell with an injection volume of 3 g, and the cell is allowed to stand at room temperature for 24 hours to allow the pre-solid liquid to fully infiltrate the battery cell, and then heated in a vacuum oven at 50°C for 24 hours to obtain an in-situ solid-state battery with an initiator.
[0113] (3) The in-situ solid-state battery is charged and formed with a small current. The specific steps of the small current charging and formation are referred to Example 1.
[0114] Performance test: The prepared in-situ solid-state battery was disassembled to observe the solidification of the electrolyte inside the battery and to perform internal resistance and charge and discharge performance tests on the solid-state battery. The results are shown in Table 1 and Figure 3 .
[0115] Table 1 Performance test results of solid-state batteries prepared in Examples and Comparative Examples
[0116]
[0117]
[0118] It can be seen from Table 1 that the embodiments of the present invention can prepare in-situ solid-state batteries without adding an initiator, and there is no liquid residue in the electrolyte. The cycle performance of the prepared solid-state battery is significantly better than that of the comparative example.
[0119] from Figure 2 and Figure 3It can be seen from the charge and discharge curves that Example 1 shows a better discharge capacity of 835.40 mAh than Comparative Example 1, which is much larger than the discharge capacity of 708.30 mAh of Comparative Example 1; similarly, the discharge capacity of Example 2, 683.20 mAh, is 2.01 times that of Comparative Example 2, 339.70 mAh.
[0120] The above results indicate that the in-situ cured battery prepared by the initiator-free curing method used in the present invention overcomes the problems of gas generation during curing and residual monomers participating in side reactions in the in-situ cured battery prepared by conventional initiators, and therefore exhibits better electrochemical properties, such as high capacity and energy density and low impedance.
[0121] from Figure 4 It can be seen that the capacity retention rate of Example 1 is significantly higher than that of Comparative Example 1, and compared with the comparative example without adding an initiator, the cycle life of the battery can be improved.
[0122] From the comparison of the test results of Example 1 and Examples 4, 5, and 6 (as shown in Table 1), it can be seen that the electrical performance of the in-situ cured battery using multiple small molecule monomers simultaneously is better than the electrochemical performance when one monomer is used alone. This is mainly because the polymer formed when multiple monomers are polymerized is a cross-linked porous network structure, which is more conducive to the migration and transmission of lithium ions.
[0123] From the comparison of the test results of Example 1 and Examples 7 and 8 (as shown in Table 1), it can be seen that when the charging voltage is lower than 3.8V, the electrolyte inside the battery cannot be completely solidified, and a large amount of unpolymerized residual monomers continuously undergo side reactions during the charging and discharging process, resulting in a sharp deterioration in the cycle performance of the battery. Therefore, the charging voltage condition should be limited to greater than or equal to 3.8V, and when the charging voltage is higher than 4.3V, although the electrolyte can be completely solidified, the battery is prone to overcharging, resulting in lithium deposition at the negative electrode, which is likely to cause thermal runaway of the battery and deteriorate the cycle performance. Therefore, the charging voltage should be less than or equal to 4.3V, and the final preferred charging voltage condition is 3.8V-4.3V.
[0124] From the comparison of the test results of Example 1 and Examples 9 and 10 (as shown in Table 1), it can be seen that when the polymerization temperature is lower than 40°C, the electrolyte inside the battery cannot be completely solidified, and a large amount of unpolymerized residual monomers will also continuously undergo side reactions during the charge and discharge process, resulting in a sharp deterioration in the cycle performance of the battery. Therefore, the polymerization temperature condition should be limited to greater than or equal to 40°C; and when the polymerization temperature is higher than 60°C, although the electrolyte can be completely solidified, the SEI film formed in the battery during the formation process will decompose at a temperature higher than 60°C, resulting in a serious decrease in the capacity and cycle performance of the battery. Therefore, the polymerization temperature should be less than or equal to 60°C, and the final preferred polymerization temperature condition is 40°C-60°C.
[0125] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An initiator-free solid-state battery, characterized in that: The solid-state battery is prepared by using a carbonate-based electrolyte, a small molecule monomer and a dry cell. The preparation method of the solid-state battery includes: Injecting the carbonate-based electrolyte into the dry cell, controlling the injection amount to be less than the designed injection amount of the dry cell; The battery cell filled with the carbonate-based electrolyte is left to stand for 8h-20h, then formed and charged to 3.8V-4.3V; the pre-solid liquid formed by the small molecule monomer and the carbonate-based electrolyte is injected into the charged battery cell so that the injection volume reaches the designed injection volume of the dry battery cell, and then heated for polymerization; the polymerization temperature is controlled to be 40°C-60°C, and the polymerization time is 12h-36h; In the pre-solidified liquid, the mass proportion of the carbonate-based electrolyte is 50%-85%, and the mass proportion of the small molecule monomer is 15%-50%; the small molecule monomer is selected from at least one of methyl methacrylate, glycidyl methacrylate, methoxy polyethylene glycol acrylate, methyl acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and pentaerythritol triacrylate.
2. The solid-state battery according to claim 1, characterized in that: The ratio of the injection amount of the carbonate-based electrolyte in the dry battery cell to the designed injection amount of the dry battery cell is (0.3-0.7):
1.
3. The solid-state battery according to claim 2, characterized in that: The ratio of the injection amount of the carbonate-based electrolyte in the dry battery cell to the designed injection amount of the dry battery cell is (0.4-0.6):
1.
4. The solid-state battery according to any one of claims 1 to 3, characterized in that: The carbonate-based electrolyte includes a lithium salt and a carbonate solvent, and the concentration of the lithium salt is 1.0 mol / L-2.0 mol / L.
5. The solid-state battery according to claim 4, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalato)borate and lithium difluorooxalatoborate.
6. The solid-state battery according to claim 5, characterized in that: The lithium salt is lithium hexafluorophosphate.
7. The solid-state battery according to claim 4, characterized in that: The carbonate solvent is at least one of ethylene carbonate, ethyl methyl carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, methyl formate, methyl acetate and ethyl propionate.
8. The solid-state battery according to claim 7, characterized in that: The carbonate solvent is a mixed solvent formed by ethylene carbonate and ethyl methyl carbonate, and the mass proportion of ethylene carbonate in the mixed solvent is 20%-40%.
9. The solid-state battery according to claim 1, characterized in that: The dry cell comprises a positive electrode sheet, a negative electrode sheet and a separator, and the positive electrode sheet is separated from the negative electrode sheet by the separator.
10. The solid-state battery according to claim 1, characterized in that: The standing temperature is 40℃-50℃.
11. A method for preparing a solid-state battery according to any one of claims 1 to 10, characterized in that: include: Injecting the carbonate-based electrolyte into the dry cell, controlling the injection amount to be less than the designed injection amount of the dry cell; The battery cell filled with the carbonate-based electrolyte is left to stand for 8 hours to 20 hours, and then formed and charged to 3.8V to 4.3V; Injecting the pre-solidified liquid formed by the small molecule monomer and the carbonate-based electrolyte into the charged battery cell so that the injection volume reaches the designed injection volume of the dry battery cell, and then heating and polymerizing; controlling the polymerization temperature to 40° C.-60° C. and the polymerization time to 12 h-36 h; In the pre-solidified liquid, the mass proportion of the carbonate-based electrolyte is 50%-85%, and the mass proportion of the small molecule monomer is 15%-50%; the small molecule monomer is selected from at least one of methyl methacrylate, glycidyl methacrylate, methoxy polyethylene glycol acrylate, methyl acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and pentaerythritol triacrylate.
12. An electrical device, characterized in that: Including the solid-state battery according to any one of claims 1 to 10 or the solid-state battery prepared by the preparation method according to claim 11.
Citation Information
Patent Citations
Method for preparing polymer electrolyte through in-situ polymerization, lithium ion battery and preparation method of lithium ion battery
CN113839096A
Semi-solid battery and manufacturing method and detection method thereof
CN117543071A